Morphometric characterization of doliniform features in the Araguaia Plain - Manchola, Oscar Eduardo Paez; Morais, Fernando de (Sociedade & Natureza, 2023)
The Araguaia Plain has extensive areas of savannah scattered forest fragments similar to circular depressions. These features, in addition to serving as corridors, could be associated with important features such as karsts, closed-water connection structures and ecological-type formations. To identify this relationship and contribute to the understanding of its genesis, this study has as its main objective the morphometric analysis of doliniform functions in the Araguaia Plain. Through the geoenvironmental characterization of the study area; digital facility models – SRTM; interpretation of Sentinel 2-A satellite images from 2019 to 2020; and calculation of morphometric variables: area, perimeters, activity, altitude, length and density, Kernel circularity index. A total of 24,023 doliniform features associated with green/healthy vegetation were identified in a Coverage Area of 114,900 km², Concentrated Majoritariate in the Brazilian municipalities of Lagoa da Confusão -Tocantins; Pium-Tocantins and Cocalinho-Mato Grosso. The features showed circular superiority areas up to 10 km², circular activity indexes at 0.5 and up to 1 and 1.5, indicating a predominance of circular shapes on slopes of 3% in the NE orientation. Based on the results, it can be verified that these features present sinkholes, as they may be under the influence of patterns associated with some processes, denoting in some processes the existence of a covered karst.